2017
DOI: 10.1097/md.0000000000009030
|View full text |Cite
|
Sign up to set email alerts
|

Association of tourniquet utilization with blood loss, rehabilitation, and complications in Chinese obese patients undergoing total knee arthroplasty

Abstract: Obesity not only gives rise to more blood loss volume but also correlates with postoperative rehabilitation and complications in surgical patients. It is not clear at present whether tourniquet utilization is associated with blood loss, rehabilitation, and complications, and it is imperative to ascertain the tactics of utilizing tourniquet in obese patients undergoing total knee arthroplasty (TKA). The present study was designed to explore the association of tourniquet utilization with blood loss, rehabilitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…[11][12][13][14][15][16] A similar finding was also observed in obese patients, where tourniquet use was not associated with reduced blood loss or increased postoperative complications following TKA. [17] Nevertheless, many reports had demonstrated reduced intraoperative blood loss and total blood loss when tourniquets were used, [18][19][20][21] whereas others found increased total blood loss resulting from hemolysis if a tourniquet was used. [22] This difference in the reported studies could be attributed to many factors, including pre-operative hemoglobin levels, surgical techniques, patient's gender, patient's age, or ethnic group.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] A similar finding was also observed in obese patients, where tourniquet use was not associated with reduced blood loss or increased postoperative complications following TKA. [17] Nevertheless, many reports had demonstrated reduced intraoperative blood loss and total blood loss when tourniquets were used, [18][19][20][21] whereas others found increased total blood loss resulting from hemolysis if a tourniquet was used. [22] This difference in the reported studies could be attributed to many factors, including pre-operative hemoglobin levels, surgical techniques, patient's gender, patient's age, or ethnic group.…”
Section: Introductionmentioning
confidence: 99%
“…To contrast, other scholars hold an opposite idea. Their studies nd that tourniquet have no signi cant impact on postoperative outcomes in TKA patients [4,11,12] . Considering the bloodless surgical eld and shorter operation time, they propose regular application of tourniquet in TKA.…”
Section: Introductionmentioning
confidence: 98%
“…Currently, many studies [ 16 19 ] have confirmed that TXA can significantly reduce intraoperative and postoperative bleeding during HTO without increasing the risk of complications. In addition, several studies have reported that forgoing routine use of tourniquets in total knee arthroplasty (TKA) using modern TXA protocols does not increase total blood loss, but facilitates rapid recovery [ 20 , 21 ]. However, there is a paucity of data that explores the effect of tourniquet use in HTO with modern TXA protocols.…”
Section: Introductionmentioning
confidence: 99%